2007
DOI: 10.2522/ptj.20060157
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Physical Activity Performance in Youth With Cerebral Palsy and Youth Who Are Developing Typically

Abstract: Background and Purpose Assessment of walking activity in youth with cerebral palsy (CP) has traditionally been “capacity-based.” The purpose of this study was to describe the day-to-day ambulatory activity “performance” of youth with CP compared with youth who were developing typically. Subjects Eighty-one youth with CP, aged 10 to 13 years, who were categorized as being in Gross Motor Function Classification System (GMFCS) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
259
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(277 citation statements)
references
References 30 publications
(27 reference statements)
13
259
4
1
Order By: Relevance
“…Accelerometer-based devices have been used by several authors to assess walking ability over several days or weeks in both household and community ambulation [33][34][35][36][37][38]. Klute et al reported that prosthetic prescription makes no differences in the step count or step rate as recorded by the StepWatch™ Activity Monitor (SAM) (OrthoCare Innovations; Mountlake Terrace, Washington) in transfemoral and transtibial amputees who are community ambulators [38].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometer-based devices have been used by several authors to assess walking ability over several days or weeks in both household and community ambulation [33][34][35][36][37][38]. Klute et al reported that prosthetic prescription makes no differences in the step count or step rate as recorded by the StepWatch™ Activity Monitor (SAM) (OrthoCare Innovations; Mountlake Terrace, Washington) in transfemoral and transtibial amputees who are community ambulators [38].…”
Section: Introductionmentioning
confidence: 99%
“…This investigation was conducted as part of a larger descriptive study of the relation between physical activity and health status and QOL in youth with CP. 14,15 The a priori hypothesis was that self-reported health status and QOL would be ordered by activity capacity and functional level, as measured by the GMFCS, such that TDY would be greater than level I, level I greater than level II, and level II greater than level III. 16 …”
mentioning
confidence: 99%
“…It is important to take into account that a minimum level of motor activity is essential in order to interact with the environment (Bjornson et al, 2007). In individuals with cognitive disorders such as CP, experiencing difficulties in movement can have serious deleterious effects on cognitive, emotional and social development (Damiano, 2006;Hughes, 1984;Taylor, Sallis, & Needle, 1985).…”
Section: Discussionmentioning
confidence: 99%